Pesantren Leadership Policies in Improving the Quality of Pesantren Learning - Novi Ariyanti (Islamic Religious Education Master Program Universitas Islam Internasional Darullughah Wadda'wah, 2026)
Pesantren face pressure in maintaining a balance between the deepening of kitab turats (classical texts) and the demands of 21st-century competencies amidst educational transformation. This imbalance has the potential to reduce the relevance of graduates if not addressed through adaptive and measurable learning policies. This study aims to analyze the leadership policies in improving the quality of learning at Pondok Pesantren Darullughah Wadda’wah Putri. The research employs a qualitative approach with a case study design. Data were collected through interviews, observation, and documentation, then analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The results show that leadership policies are implemented integratively through participatory planning, professionalism-based execution by the asatidzah (teachers), and continuous evaluation. These policies are able to integrate salaf (traditional) values with a hadhari (civilizational) approach as well as the strengthening of 21st-century skills, thereby creating an adaptive learning ecosystem and producing competent graduates with character.